Tribological behavior of molybdenum disulfide and tungsten disulfide sprayed coatings in low viscosity hydrocarbon environments. (January 2023) - Cairns, E.; Ayyagari, A.; McCoy, C.; Berkebile, S.; Berman, D.; Aouadi, S.M.; Voevodin, A.A.
Abstract: The tribological behavior of MoS2 and WS2 transition metal dichalcogenide (TMD) spray coatings in low-viscosity hydrocarbon environments was investigated. Sliding tests were performed in two hydrocarbons – hydrophilic ethanol and hydrophobic dodecane and were compared to tests in humid air and dry nitrogen conditions. Coating steel surfaces decreased friction across all test conditions, with the largest and most sustainable decreases being in dry nitrogen and dodecane environments, where friction coefficients of less than 0.1 were sustained. Analysis was performed using scanning electron microscopy, Raman spectroscopy, and x-ray photoelectron spectroscopy. Friction reductions in dodecane were explained by reduced oxidation of the coating, due to protection from the hydrophobic hydrocarbon film, allowing basal plane alignment and uninhibited sliding of TMD sheets. Highlights: Transition-metal dichalcogenide (TMD) solid lubricants can be used synergistically with low lubricity fuels and synthetic oils. Pin-on-disk tests reported for MoS2 adn WS2 coatings on steel coupons in humid air, dry nitrogen, ethanol, and dodecane. Synergistic low friction and wear behavior was shown for TMD coatings in dodecane, whereas ethanol promoted coating wear.